Endometrial Cytology and Cervical Mucus Characteristics of Repeat Breeding Crossbred Cows in Relation to Post-Treatment Fertility - Raval, S.R.; Panchal, M.T.; Dhami, A.J.; Parmar, S.C. (Indian Journal of Veterinary Sciences and Biotechnology, 2018)
The present study was conducted on repeat breeder (RB, n=40) crossbred cows under field conditions to evaluate their endometrial cytology and cervico-vaginal mucus (CVM) characteristics in relation to post-treatment fertility. The endometrial cytology was obtained using cytobrush technique and CVM by aspiration technique from vaginal fornix using sterile pipette and syringe. The cows yielding bacterial growth in CVM were treated with sensitive antibiotics (i/m) for 3-5 days (Gr I, RBT: 28) and cows not yielding bacterial growth (control, Gr II, RBC: 12) were given 10 ml of normal saline (i/m). The cows were inseminated at subsequent estrus and followed for repeating to estrus and/or pregnancy. The subclinical endometritis was diagnosed using endometrial cytology (PMN%: > 4%) in cows yielding bacterial isolates (n=28) with mean PMN% of 21.80±8.39, 32.18±3.26 and 29.25±6.63 for those having clear stringy consistency, turbid viscous, and watery white flaky CVM, respectively. The mean PMN% in RB cows with no bacterial isolates (n=12) and having clear stringy CVM was 1.50±0.23. The mean values of spinnbarkeit (cm), pH and Whiteside test scores of CVM were 14.60±0.51, 5.82±0.85 and 3.00±0.17; 7.41±0.15, 7.44±0.21 and 7.08±0.19; and 1.40±0.60, 1.91±0.28, and 1.75±0.25, respectively, for culturally positive cows having CVM of clear stringy, turbid viscous and watery with white flakes, respectively (Group I). The mean spinnbarkeit (cm), pH and Whiteside test scores in control cows not yielding any bacterial isolates and having clear stringy CVM (Group II) were 13.08±0.99, 7.37±0.10 and 0.33±0.19. The RB cows with clear stringy, turbid viscous and white flaky CVM and yielding bacterial isolates had mean inter-estrus intervals of 18.80 ±0.51, 15.91±0.48 and 13.83±0.41 days, respectively, the differences being significant (P
Keywords: Crossbred cows; Repeat breeding; Cytobrush; Endometrial cytology; Whiteside test; Spinnbarkeit; Association with Fertility